2012
DOI: 10.1086/663691
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Responses in Structured Populations Pave the Way to Group Optimality

Abstract: An unresolved controversy regarding social behaviors is exemplified when natural selection might lead to behaviors that maximize fitness at the social-group level but are costly at the individual level. Except for the special case of groups of clones, we do not have a general understanding of how and when group-optimal behaviors evolve, especially when the behaviors in question are flexible. To address this question, we develop a general model that integrates behavioral plasticity in social interactions with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
185
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(197 citation statements)
references
References 68 publications
12
185
0
Order By: Relevance
“…Akçay & Simms [29] showed in the legume-rhizobium mutualism that both directed feedback (as produced by a negotiation process) and undirected ones are needed to maintain cooperation in rhizobia. Similarly, Van Cleve & Akçay [30] showed that phenotypic feedback and population structure within and between species reinforce each other's effect, consistent with results from within-species social evolution theory [7,31,32]. Here, I focus on three major types of fitness feedback in the context of mutualistic symbioses: partner choice, population structure and different kinds of phenotypic feedback from the host.…”
Section: Introductionsupporting
confidence: 55%
“…Akçay & Simms [29] showed in the legume-rhizobium mutualism that both directed feedback (as produced by a negotiation process) and undirected ones are needed to maintain cooperation in rhizobia. Similarly, Van Cleve & Akçay [30] showed that phenotypic feedback and population structure within and between species reinforce each other's effect, consistent with results from within-species social evolution theory [7,31,32]. Here, I focus on three major types of fitness feedback in the context of mutualistic symbioses: partner choice, population structure and different kinds of phenotypic feedback from the host.…”
Section: Introductionsupporting
confidence: 55%
“…Those who gain more from such investment will then invest more, whereas those who gain less will invest less and free-ride to a greater extent on the efforts of others, but all are nevertheless still indifferent to the distribution of resources. There has been much discussion recently in the biological literature of transitions between levels of selection, with models exploring the circumstances under which selection might come to favour traits and behaviours that maximize group rather than individual fitness [9,14]. A frequent assumption in these discussions is that the same processes that favour cooperation in one behavioural context will favour cooperation in all.…”
Section: Discussionmentioning
confidence: 99%
“…We consider a population where individuals are genetically related to each other, which we characterize by the (demographically scaled) relatedness coefficient r (Lehmann and Rousset 2010; Akçay and Van Cleve 2012). In general, this scaled relatedness coefficient will be a function of variables such as migration rate and group size.…”
mentioning
confidence: 99%
“…, where m and s are the migration rates between m)s} groups and survivorship, respectively (Taylor and Irwin 2000;Akçay and Van Cleve 2012). In different biological scenarios, relatedness will vary with group size in different ways, though in general, it is expected to decrease with increasing group size.…”
mentioning
confidence: 99%
See 1 more Smart Citation